PENGARUH KUALITAS LAYANAN DAN KEPEMIMPINAN PENGURUS TERHADAP PARTISIPASI ANGGOTA PADA KOPERASI SAWIT BERSAMA (KSB) AIR HAJI KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Rahmi, Dewi; Yulihardi, Yulihardi; Amaluis, Dina (Pendidikan Ekonomi, 2014)
ABSTRAK Issues raised in this study is " relatively low participation of members of Koperasi Sawit Bersama Air Haji  Kecamatan Sungai Aur Kabupaten Pasaman Barat " . The variables of this study is the Quality of Service ( X1 ) , Leadership Board ( X2 ) , Member Participation ( Y ) . This study aims to identify and analyze ( 1 ) Effect of service quality on the participation of members of the KSB Air Haji . ( 2 ) Effect on the participation of members of the leadership committee on KSB Air Haji  . ( 3 ) Effect of quality of service and leadership to the board member s participation in the   . KSB Air Haji This research is descriptive associative . The samples in this study were 103 members by using a sampling technique that Stratifed Sampling done in proportional . The data collection technique used was a questionnaire . Before the questionnaire is used to obtain the data , to test the validity and reliability . The data analysis technique used is descriptive analysis and inductive analysis . To test the hypothesis used the t test , F test and the coefficient determinant ( ) .The conclusion from the results of this study indicate that ( 1 ) There is a significant and positive effect between quality of service to the participation of members of the KSB Air Haji  . ( 2 ) There is a positive and significant effect on the participation of the leadership board member at KSB Air Haji  . ( 3 ) There is a significant relationship between quality of service and leadership to the board simultaneous participation of members of the KSB Air Haji . Based on this study it is suggested to the management to always improve the quality of service and leadership in serving the community board so that members are increasingly active in participating actively to make loans on KSB Air Haji